ANALISIS UJI GETARAN TERHADAP KUALITAS HASIL PENGEBORAN MESIN DRILING KNUTH TYPE KB 20 S - Halman; Roberth Ratlalan; Multhazam (Program Pendidikan Vokasi Teknik Mesin, 2025)
The drilling process is one of the most important machining processes in the manufacturing industry because it directly affects the dimensional accuracy, surface smoothness, and integrity of the workpiece material. One of the problems that often arise in the drilling process is machine vibration which can reduce the quality of the hole results. This study aims to analyze the effect of vibration levels on the quality of drilling results on a Knuth KB 20 S drilling machine. The research method used is an experimental method by conducting drilling tests at several variations in spindle rotational speed and feed rate. Vibration measurements were carried out using a vibration meter, while the quality of drilling results was evaluated based on the parameters of surface roughness, hole diameter, and tool wear level. The results showed that an increase in vibration amplitude was directly proportional to an increase in surface roughness and deviations in hole diameter. In addition, high vibration also accelerated the wear of the drill bit. Based on the results of the study, the highest vibration spike occurred in the initial start-up phase at the machine head with a value of 1.7 mms, which has the potential to cause mismatches in the initial hole dimensions and an increase in the surface roughness of the drilling results. After the initial phase, vibration levels decreased drastically and stabilized in the range of 0.2 to 0.3 mms, indicating that the machine had reached a more balanced and stable operating condition. Furthermore, the transfer of vibration to the table and the machine stand, particularly during the transition phase with vibration values ​​reaching 0.6 mms at the stand, indicated the need for structural reinforcement to prevent resonance that could affect the machine's stability and overall drilling quality.